Metodická příručka participativního bydlení - Káňová, Markéta; Kubala, Petr; Orcígr, Václav; Tichý, David (Masaryk University Press, 2024)
Title in English: Methodological Guide to Participatory Housing Participatory housing means that residents are involved in the preparation, investment and management of all or part of the housing project. There are a number of reasons why residents engage in participatory housing projects: as a response to declining housing affordability, to improve the quality of housing and its architectural design, to increase resilience to the climate crisis, or to improve neighbourhood relations. Household cooperation and coordination is transforming relationships in housing construction and management. In this situation, residents are not passive recipients of municipal housing policies, nor are they individual, independent households that only address their housing situation in the housing market. This methodology presents them as actors in the construction and management of housing, as neighbours and as natural partners of the municipality. The aim is to outline the ways in which municipalities can support and develop participatory housing, and to discuss the limitations of this approach.